Examining the Challenges Faced in the Preservation of Electronic Records in Local Government: A Case Study of Ntungamo District Local Government. - Muhumuza, Barnabas (Kabale University, 2024)
The study aimed at examining the challenges faced in the preservation of electronic records in local government case study of NDLG. It was guided by the following research objectives; to identify electronic records preservation methods used in Ntungamo District Local Government, to find out challenges faced in preservation of electronic records in Ntungamo District Local Government and to suggest the solutions to challenges faced in preservation of electronic records of Ntungamo district local government. The study employed a descriptive research design. From the study findings, Electronic Records preservation methods included; using emails, through data back, through administering passwords and saving files well. • The study findings indicated that large format files, a virus that attacks files, poor location of files, poor naming of files, expense in making backups and deleting files accidentally were challenges faced in the preservation of electronic records in Ntungamo District Local Government. The study findings also revealed that making backups, installing antivirus software, using passwords, deleting carefully unwanted files, allocating files well, and saving files well were the solutions to Challenges Faced in the Preservation of electronic records in Ntungamo District Local government. The researcher recommended that the government should also provide adequate ICT tools to the local government departments to be able to preserve the electronic records well. This also provides an easy flow of information throughout the departments of the local government.